QUALITY MANAGEMENT IMPLEMENTATION IN MI ISKANDAR SULAIMAN, BATU CITY - Qurrotul Qurrotul A'yun Sufyan (re-JIEM (Research Journal of Islamic Education Management), 2022)
The purpose of this research is to describe how school management is implemented in improving the quality of education at MI Iskandar Sulaiman, Batu City. This research use desciptive qualitative approach. Data collection techniques were carried out by interviews, observation, and documentation. The indicators developed by researchers as a guide in data collection related to the implementation of school management include school planning, implementation of school programs. Data analysis techniques include data reduction, data presentation, and drawing conclusions. Data validity test was carried out by technique triangulation and source triangulation. The educational process at MI Iskandar Sulaiman Batu has met the criteria for quality education which includes: 1) the effectiveness of the principal's leadership; 2) active participation of all components with an interest in the school; 3) the effectiveness of the teaching and learning process; 4) relevant curriculum; 5) vision, mission, and goals that are directed, systemized so that they are expected to be achieved; 6) conducive atmosphere and school environment; 6) involvement between the community and parents of students. Then the impact of this research is that the leadership and managerial abilities of school principals are a must for realizing effective madrasah management and of course in accordance with the times.